Superiority of temozolomide over radiotherapy for elderly patients with RTK II methylation class, MGMT promoter methylated malignant astrocytoma. Issue 8 (17th February 2020) - Wick, Antje; Kessler, Tobias; Platten, Michael; Meisner, Christoph; Bamberg, Michael; Herrlinger, Ulrich; Felsberg, Jörg; Weyerbrock, Astrid; Papsdorf, Kirsten; Steinbach, Joachim P; Sabel, Michael; Vesper, Jan; et al.
Abstract: Background: O 6 -methylguanine DNA-methyl transferase ( MGMT ) promoter methylation status is predictive for alkylating chemotherapy, but there are non-benefiting subgroups. Methods: This is the long-term update of NOA-08 (NCT01502241), which compared efficacy and safety of radiotherapy (RT, n = 176) and temozolomide (TMZ, n = 193) at 7/14 days in patients >65 years old with anaplastic astrocytoma or glioblastoma. DNA methylation patterns and copy number variations were assessed in the biomarker cohort of 104 patients and in an independent cohort of 188 patients treated with RT+TMZ-containing regimens in Heidelberg. Results: In the full NOA-08 cohort, median overall survival (OS) was 8.2 [7.0–10.0] months for TMZ treatment versus 9.4 [8.1–10.4] months for RT; hazard ratio (HR) = 0.93 (95% CI: 0.76–1.15) of TMZ versus RT. Median event-free survival (EFS) [3.4 (3.2–4.1) months vs 4.6 (4.2–5.0) months] did not differ, with HR = 1.02 (0.83–1.25). Patients with MGMT methylated tumors had markedly longer OS and EFS when treated with TMZ (18.4 [13.9–24.4] mo and 8.5 [6.9–13.3] mo) versus RT (9.6 [6.4–13.7] mo and 4.8 [4.3–6.2] mo, HR 0.44 [0.27–0.70], P < 0.001 for OS and 0.46 [0.29–0.73], P = 0.001 for EFS). Patients with glioblastomas of the methylation classes receptor tyrosine kinase I (RTK I) and mesenchymal subgroups lacked a prognostic impact of MGMT in both cohorts. Conclusion: MGMT promoter methylation is a strong predictive biomarker for the choice between RT and TMZ. It indicates favorable long-term outcome with initial TMZ monotherapy in patients with MGMT promoter-methylated tumors primarily in the RTK II subgroup.